Beliefs and attitudes of Australian learner drivers toward driving and avoiding driving through floodwater. (April 2023) - Hamilton, Kyra; Keech, Jacob J.; Peden, Amy E.; Hagger, Martin S.
Highlights: Driving through floodwaters is a leading cause of flood-related death, injury, and rescue. Little is known about learner driver beliefs in times of flood. We used the theory of planned behaviour across formative and predictive studies. Social cognition factors and past behaviour predicted driver willingness. Theory-based targets should be the basis of intervention programs for novice drivers. Abstract: Introduction: Driving through floodwater is a significant cause of flood-related injury and mortality, and opportunities exist to embed safe driving messages regarding floodwaters to novice drivers in graduated driver licensing schemes. To inform future educational efforts, we investigated the beliefs and attitudes of Australian learner drivers about driving and avoiding driving through floodwaters. Methods: The study adopted a cross-sectional correlational design with measures drawn from the theory of planned behaviour and administered within an online survey. Phase 1 ( N  = 44 learner drivers) aimed to identify the core beliefs associated with driving through floodwater. Phase 2 ( N  = 250 learner drivers) tested these beliefs predicting willingness to drive through floodwater as well as the social psychological factors that predict learner drivers' willingness to drive and avoid driving through floodwater using a pre-tested scenario. Analyses comprised descriptive statistics, linear regression, and structural equation models. Results: Ten key beliefs were identified as predicting willingness to drive through floodwater. These included perceived advantages and disadvantages, perceived social approval from important others, and perceived facilitators and barriers regarding driving through floodwater in the presented scenario. Structural equation models of social cognition constructs of the theory of planned behaviour revealed attitude, subjective norm, and perceived behavioural control predicted both willingness to drive and avoid driving through floodwater. Past experience as a passenger also predicted these social cognition constructs, although this differed across models. Discussion: Results highlight the importance of modelling safe driving behaviour for young passengers. The strong association between subjective norm and willingness to drive through floodwater further highlights the importance of those supervising learner drivers to establish expectations around avoiding driving through the floodwater if it is encountered on a driving route. Conclusion: Social cognition factors from the theory of planned behaviour predict willingness to drive and avoid driving though floodwater. Theory-based targets should be considered for the development of intervention programs for novice drivers, such as those holding learner licenses.